GAMBARAN KECERDASAN EMOSIONAL SISWA DI SMK MUHAMMADIYAH 3 KADUNGORA - Wiwi Juwita; Euis Eti Rohaeti; Devy Sekar Ayu Ningrum (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
This study aims to determine the description of the emotional intelligence of students at SMK Muhammadiyah 3 Kadungora. The approach taken is quantitative. The quantitative approach is a systematic scientific research method using statistical data analysis, namely using mathematical models, theories and / or hypotheses related to phenomenon, both in parts and in their relationships. The research sample consisted of 37 grade X students of SMK Muhammadiyah 3 Kadungora who had low emotional intelligence, namely 30 students. This is indicated by an attitude of disappointment, anger, hatred and so on, if left alone, it will affect the health of adolescent personalities. Especially students become unable to process their emotional intelligence. Data collection techniques use questionnaires and observations. Based on the results of questionnaires and field research, it was concluded that the description of emotional intelligence of class X SMK Muhammadiyah 3 Kadungora students could affect the level of student learning progress.Keywords: Emotional Intellegence, Students